Demographic and physiological factors associated with clinically significant eyelid edema in patients following upper eyelid surgery. (March 2023) - Zhang-Nunes, Sandy; Guo, Sarah; Li, Joy; Mehta, Preeya; Yu, Roy; Shen, Alice; Bokman, Christine; Yau, Anita; Chang, Jessica R.
Summary: Purpose: To investigate demographic and physiological variables associated with clinically significant edema after upper eyelid surgery. Methods: A retrospective chart review was performed on patients who underwent blepharoplasty or external levator advancement with or without lid crease formation between January 2018 and January 2021 at the University of Southern California. Age, sex, pertinent medical history (medications causing edema and comorbidities), and pertinent surgical procedures were all collected. Postoperative photos were graded by two independent physician graders on a newly developed photographic scale ranging from 0 (no edema) to 3 (severe edema). Clinically significant edema of the eyelids was defined as Grade 3 edema at any postoperative point or ≥ Grade 1 edema after 90 days post operation. Patients without postoperative photos were excluded. Mann–Whitney U test, Fisher's exact test, and χ2 test were used to compare groups with and without significant edema. All analyses were conducted using SAS version 9.4 (SAS Institute Inc.) with α=0.05. Results: Out of 217 patients, East Asian participants had higher odds of developing edema than White participants (odds ratio, 7.92; CI, 3.15–19.93, p < 0.0001) and Hispanic participants (odds ratio, 3.47; CI, 1.51–7.97, p  = 0.003). Southeast Asian participants also had higher odds of developing CSEE than White participants (odds ratio, 6.19; CI, 1.71–22.43, p  = 0.006). Fifty-four (24.9%) patients had clinically significant edema. Although BMI, medical comorbidities, medication use, and age did not affect edema, there was a statistically significant relationship between race and incidence of edema ( p  = 0.0001). Those in the CSEE group were also more likely to require reoperation ( p  = 0.0143). Conclusions: There is a statistically significant relationship between Asian race and the incidence of clinically significant eyelid edema. CSEE is associated with a higher incidence of reoperation